1993
DOI: 10.1079/bjn19930108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pattern of food intake on human energy metabolism

Abstract: The pattern of food intake can affect the regulation of body weight and lipogenesis. We studied the effect of meal frequency on human energy expenditure (EE) and its components. During 1 week ten male adults (age 25-61 years, body mass index 20.7-30.4 kg/m2) were fed to energy balance a t two mealsld (gorging pattern) and during another week at seven meals/d (nibbling pattern). For the first 6 d of each week the food was provided at home, followed by a 36 h stay in a respiration chamber. 0, consumption and CO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 28 publications
0
44
1
Order By: Relevance
“…This is supported by previous studies showing that total energy expenditure is not affected by meal frequency, which suggests that any effects of snack consumption on body weight are mediated through energy intake and not energy expenditure. 7,25,26 Surprisingly, we found that energy density had no effect on body weight changes. It was previously shown that energy density increased total daily energy intake.…”
Section: Discussioncontrasting
confidence: 55%
“…This is supported by previous studies showing that total energy expenditure is not affected by meal frequency, which suggests that any effects of snack consumption on body weight are mediated through energy intake and not energy expenditure. 7,25,26 Surprisingly, we found that energy density had no effect on body weight changes. It was previously shown that energy density increased total daily energy intake.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies assessing the effect of meal frequency on total energy expenditure report no statistical association between these two factors. 15,[26][27][28] However, poor definition of the key variables hampers the interpretation and comparison of these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the effect of meal frequency on total energy expenditure report no statistical association between these two factors. 15,[26][27][28] Studies evaluating the effect of meal frequency on thermic effect of foods (TEF) have suggested contradictory results. [29][30][31][32] It seems that Western populations are increasingly moving away from regular meals towards marked interdaily variation in frequency and time of consumption of food.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such measurement tools may 357 also lack both reliability and sensitivity when applied to subtle changes across all aspects of 358 physical activity thermogenesis (62) . While these issues of reliability and sensitivity have been 359 overcome using doubly-labelled water to verify no difference in total energy expenditure between 360 a two-versus seven-meal daily feeding pattern (63) , that finding is not specific to breakfast or physical activity thermogenesis per se, nor does the technique reveal temporal patterns of 362 activity.…”
mentioning
confidence: 99%